Analisis Ikonoklasme Nurcholish Madjid pada Kaligrafi Abdul Djalil Pirous - Akhyar Fahrudin (Jurnal Riset Agama, 2022)
The purpose of this. study was to analyze iconoclasm in A.D. Pirous's calligraphy using Nurcholish Madjid's iconoclasm theory. The method used in this research is a literature review. The results and discussion of this research include the biography of A.D. Pirous, the theory of iconoclasm of Nurcholish Madjid, and the analysis of iconoclasm in A.D. Pirous's calligraphy paintings. This study concludes that A.D. Pirous is an Acehnese Muslim artist who developed calligraphy in Indonesia. By establishing his school, Pirous calligraphy created a new style in Islamic art in Indonesia. According to Nurcholish Madjid, Islam is a religion that still applies the concept of iconoclasm in its teachings, including those related to works of art such as calligraphy. The analysis of Nurcholish Madjid's iconoclasm on A.D. Pirous's calligraphy can be seen from two aspects: the release of Pirous in following the rules of calligraphy and the elimination of the sacredness his calligraphy. This research is recommended for further and in-depth research on calligraphy painting or other works of art and the use of iconoclasm theory as an analytical tool, especially Nurcholish Madjid's iconoclasm and other theological studies.